FACTORS OF DIGITAL TRANSFORMATION OF AN ENTERPRISE IN THE CONTEXT OF DIGITALIZATION - HLADKYI, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the relevance of determining and assessing the impact of digital transformation factors on the activities of an enterprise in the context of digitalization. The importance of the innovative and technological activities of the enterprise, which is due to the high pace of digitalization and digitization, is highlighted. The factors of the digital transformation of the enterprise are considered based on its material and technical support, where the main attention is paid to the processes of modernization, renewal, high-quality formation and effective use of fixed assets. The importance of combining the adaptation of the enterprise to the impact of digital transformation factors with the adoption and implementation of management decisions is substantiated, where the introduction of digital technologies is envisaged with a simultaneous increase in the intensity of use of the active part of fixed assets. The following priority areas of enterprise development in the context of digitalization are associated with material and technical support, such as intellectualization of labor, information and communication technologization, maximization of production capacity, innovativeness of production and sales of products. The impact of digitalization is constantly increasing and to which enterprises need to adapt qualitatively, which requires the development and implementation of new approaches to improving the management system, where the impact of digital transformation factors will be taken into account first of all. Digitalization and digitization technologies are being implemented on an ever larger scale and cover vital areas of business development and are critically important in the development of new types of activities. Solving the tasks of increasing the efficiency of providing digital technologies from the management of the enterprise requires improving the management system, which will be focused on identifying and assessing the impact of digitalization and digitization factors.